The Influence of Green Fintech Adoption and ESG Awareness on the Financial Performance of Startups in West Java - Hasmia Melati Arifin; Dila Padilah Nurhasanah; Paramita Andiani (Westscience Press, 2026)
This study investigates the effect of green fintech adoption and ESG (Environmental, Social, and Governance) awareness on the financial performance of startups in West Java. A quantitative research design was employed using primary data collected from 85 startup actors through structured questionnaires measured on a five-point Likert scale. Data analysis was conducted using SPSS version 25, including validity and reliability testing, classical assumption tests, and multiple linear regression analysis. The results indicate that green fintech adoption has a positive and significant effect on financial performance, suggesting that the use of environmentally oriented financial technologies enhances operational efficiency and financial outcomes. ESG awareness also demonstrates a positive and significant influence, indicating that startups with stronger sustainability orientation achieve better financial results. Simultaneously, both variables significantly affect financial performance, with a coefficient of determination (R²) of 0.543, meaning that 54.3% of the variance in financial performance is explained by the model. These findings highlight the strategic importance of integrating digital financial innovation with sustainability awareness to achieve sustainable financial growth in startups.